A Study on Drug Utilization Review and Potential Drug-Drug Interactions in Chronic Kidney Disease Patients (Global Journal of Medical Research, 2018)
Abstract not found
Keywords: chronic kidney disease (CKD); drug-drug interactions (DDIs); drug utilization review (DUR)